Strengthh and physical properties of planted timber species in Sarawak - Ngu, Siew Ling (Universiti Malaysia Sarawak, (UNIMAS), 2010)
The realization has grown that many earth's resources are non-renewable. Hence, it is necessary to develop a more sustainable construction technology that employs renewable construction material as the main structural element. Therefore, secondary timber as Acacia mangium and Shorea Macrophylla with fast growing time, durable and high strength properties has chooses to study to act as an alternative for the construction of the building. Basic information on mechanical properties for promoting effective utilization of Sarawak timber species as construction materials was tabulated. The relationship between basic density and modulus of rupture (MOR), modulus of elasticity (MOE) and compressive strength of small clear specimens were investigated. Based on the Malaysia Grading Rule (1984), the basic density for Acacia mangium and Shorea Macrophylla is classified under light hardwood and softwood respectively. Besides, Acacia mangium and Shorea Macrophylla under Strength Group C and D respectively. There is a direct relationship between physical properties and strength properties, and this is prove by Dr. Alik Duju where he found out that there is linear relationship between basic density and the strength properties were found by linear regression. The higher the moisture contents of a timber, the lower the basic density of that timber. As the basic densities are lower, all the strength properties of the timber will be affect and become lower. Throughout relevant study and effective further laboratory work, it can increase the strength of these fast growing timbers for further utilization of timber in construction.